Exploration of unhealthy food consumption patterns in Sleman region by interprofessional undergraduate health students - Lastdes Cristiany Friday; Doni Widyandana; Nandyan Nurlaksana Wilastonegoro; Fitriana Fitriana; Dessy Christine Hosianna; Haidar Zain; Indah Dwi Setyaningrum; Gandes Retno Rahayu (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2020)
Despite the average life expectancy of Indonesian people increasing from 63.63 in 1990 to 71.69 in 2016, the gap of life expectancy and healthy age life expectancy also increased from 7.49 to 8.72. RISKESDAS (2018) further highlighted that the proportion of Indonesian people with a healthy diet was poor. These data challenged us to implement an outreach program, Community and Family Health Care – Interprofessional Education (CFHC-IPE), involving our medicine, nursing and nutrition students for assisting families and communities with an aim of improving the population health status. Thus, we assessed their baseline status, in particular, people’s dietary habits. We attached batch 2015 and 2016 students to 465 households with 1,254 family members. We deployed them to 15 different sub-villages in Sleman Regency, Yogyakarta. Students surveyed the families and put the data in family folders during field visits in 2018 – 2019. Our focus was to seek eating patterns of the families and performed descriptive analysis of socio-demographic aspects within those with certain dietary habits using chi-squared tests. Of the 1,254 family members, those who routinely consume fried, sweetened, contained preservatives and grilled foods were 70.14%, 61.00%, 38.13%, and 20.08%, respectively. We found the adults tend to consume more sweetened foods and beverages along with grilled foods compared to the elderly, and the differences of proportions are statistically significant. The CFHC-IPE program partner families were often not realizing that a combination of their dietary habits, in particular, the consumption of fried and sweetened meals might result in threats to the family members’ health. Fried foods were the most routinely consumed followed by sweetened food, grilled foods and foods containing preservatives. These patterns were also the same in both urban and rural settings.